MODEL EDUKASI ANTI-NARKOBA MELALUI PELATIHAN DESAIN POSTER BAGI SISWA SMP - Ahmad Nur Cahyo; Andi Anugrah Batari Fatimah; Rafika Rasdin (Institut Teknologi dan Bisnis Swadharma, 2026)
Drug abuse among adolescents, particularly junior high school students, is becoming a growing concern in Indonesia. The spread of drugs among students is often driven by unhealthy social influences, ignorance about the harmful effects of drugs, and increasingly easy access through social media and digital platforms. To address this issue, a Community Service (PKM) program titled